2014
DOI: 10.1167/iovs.14-14038
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Diffusion and Edema With Modern Scleral Rigid Gas Permeable Contact Lenses

Abstract: PURPOSE. We defined the theoretical oxygen tension behind modern scleral contact lenses (CLs) made of different rigid gas permeable (RGP) materials, assuming different thickness of the tear layer behind the lens. A second goal was to show clinically the effect of the postlens tear film on corneal swelling. METHODS.We simulated the partial pressure of oxygen across the cornea behind scleral CLs made of different lens materials (oxygen permeability Dk, 75-200 barrer) and different thickness (T av , 100-300 lm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
93
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 32 publications
5
93
0
2
Order By: Relevance
“…Pullum and Stapleton [30] described a less than 3% corneal swelling in four healthy subjects with scleral lenses. Depending on the thickness of the fluid layer between lens and cornea, a corneal swelling of 1.5-4% in eight healthy subjects was reported recently by Compañ et al [32] When comparing scleral lens Dk, it seems that Pullum and Stapleton used lower scleral lens Dk's, and the group of Compañ et al used comparable Dk's compared to our study. The limited temporary increase in pachymetry in our study group was not expected to cause adverse physiological corneal responses; however, individual hypoxia responses may differ.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Pullum and Stapleton [30] described a less than 3% corneal swelling in four healthy subjects with scleral lenses. Depending on the thickness of the fluid layer between lens and cornea, a corneal swelling of 1.5-4% in eight healthy subjects was reported recently by Compañ et al [32] When comparing scleral lens Dk, it seems that Pullum and Stapleton used lower scleral lens Dk's, and the group of Compañ et al used comparable Dk's compared to our study. The limited temporary increase in pachymetry in our study group was not expected to cause adverse physiological corneal responses; however, individual hypoxia responses may differ.…”
Section: Discussionsupporting
confidence: 71%
“…The limited temporary increase in pachymetry in our study group was not expected to cause adverse physiological corneal responses; however, individual hypoxia responses may differ. In general, it is recommended to restrict hypoxia-induced swelling by application of highest Dk available materials and minimizing both lens thickness and the fluid layer between lens and cornea [31,32]. The thickness of the fluid layer between lens and cornea was not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, part clinical and part theoretical, Compañ et al [5] calculated that to avoid corneal edema during open eye wear a scleral contact lens of 200 m thickness and made from a material of at least 125 Dk must not be fitted with a corneal vault greater than 150 m. Subjects fitted with 15.5 mm, 100 Dk material scleral contact lenses and a post-lens tear film thickness along visual axis of 150 m or 350 m had a corneal swelling of 1.6% for the shallower and 3.9% for the deeper reservoir after 3 h wearing time. This magnitude of swelling is within the range of the physiological swelling experienced during closed eye conditions, such as sleep [6,7].…”
mentioning
confidence: 95%
“…The above mentioned studies [5,8] reported 1.6-3.9% corneal swelling after scleral lens wear, which is a level of edema not detectable during a normal biomicroscopical corneal evaluation. In a retrospective study on 517 eyes it was reported that 7.4% experienced episodes of edema [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation